Memória e economia afetiva nas produções em Live-action: Aladdin e o Rei Leão - D’altoé, Francisca (2020)
Analyzing the fragments of memory present in the digital environment, the dissertation aims to verify how the live-action productions, Aladdin and The Lion King awaken the affective memory of their target audience, while permeating other current issues, such as: media convergence and the affective economy. The methodology used in this research is the content analysis and the theories of Maurice Halbwachs, regarding the collectivity of memories and their social relevance, and Henry Jenkins, a theorist of the convergent communication and the cultural impacts of media propagation. The results achieved demonstrate a high prominence for the commercialization of nostalgia and the updating of journeys with the objective of reaching distinct target audiences while reinforcing ties between media products and their fan communities.